2021
DOI: 10.3389/fcvm.2020.623012
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling Reveals the Shared and Distinct Transcriptional Signatures in Human Lung Epithelial Cells Infected With SARS-CoV-2, MERS-CoV, or SARS-CoV: Potential Implications in Cardiovascular Complications of COVID-19

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative virus for the current global pandemic known as coronavirus disease 2019 (COVID-19). SARS-CoV-2 belongs to the family of single-stranded RNA viruses known as coronaviruses, including the MERS-CoV and SARS-CoV that cause Middle East respiratory syndrome (MERS) and severe acute respiratory syndrome (SARS), respectively. These coronaviruses are associated in the way that they cause mild to severe upper respiratory tract illness. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 43 publications
(37 reference statements)
6
39
0
Order By: Relevance
“…Moreover, two recent publications demonstrated that infection of various lung epithelial cells with SARS-CoV-2 leads to decreased expression of the α 1 -, α 2 -, α 3 -, β 1 -, and β 3 -subunits of the Na,K-ATPase at the transcriptional level ( 48 , 49 ). Similar results were obtained in another study, which documented reduced gene expression of the Na,K-ATPase β 1 -subunit upon infection of human lung epithelial cells with SARS-CoV-2 ( 50 ). In addition, differential gene expression analysis of postmortem lung tissue samples from patients with COVID-19 revealed significant downregulation of gene expression of the Na,K-ATPase α 1 -subunit ( 48 ).…”
Section: Direct Effects Of Sars-cov-2 Infection On Expression Maturation and Trafficking Of Nak-atpase In Infected Cellssupporting
confidence: 88%
“…Moreover, two recent publications demonstrated that infection of various lung epithelial cells with SARS-CoV-2 leads to decreased expression of the α 1 -, α 2 -, α 3 -, β 1 -, and β 3 -subunits of the Na,K-ATPase at the transcriptional level ( 48 , 49 ). Similar results were obtained in another study, which documented reduced gene expression of the Na,K-ATPase β 1 -subunit upon infection of human lung epithelial cells with SARS-CoV-2 ( 50 ). In addition, differential gene expression analysis of postmortem lung tissue samples from patients with COVID-19 revealed significant downregulation of gene expression of the Na,K-ATPase α 1 -subunit ( 48 ).…”
Section: Direct Effects Of Sars-cov-2 Infection On Expression Maturation and Trafficking Of Nak-atpase In Infected Cellssupporting
confidence: 88%
“…Thus, discovering the unique transcriptional feature of COVID-19 may supplement the diagnostic strategy of COVID-19, especially the signature of host response. Notably, SARS-CoV-2-induced changes of gene expressions has reported to potentially distinguish COVID-19 from other infections (e.g., MERS-CoV and SARS-CoV), in which IFN-I genes is involved in the unique biosignature in response to SARS-CoV-2 infection ( 32 ). However, ISGs can be triggered by various stimulators.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, FitzGerald and colleagues showed that this prothrombotic response may be unique to SARS-CoV-2 and not shared by other respiratory viruses such as influenza A, which did not significantly alter the expression levels of genes involved in the coagulation pathway. Consistent with this notion, a recent study has shown a significant relationship of genes related to coagulation (e.g., F3, PROS1, ITGB3, and TFPI2 ) with SARS-CoV-2 but not to other human coronaviruses (e.g., Middle East Respiratory Syndrome coronavirus [MERS-CoV] and severe acute respiratory syndrome coronavirus [SARS-CoV]) ( 9 ). Together, these data suggest that SARS-CoV-2 coaxes a unique response in the epithelial cells and alveolar macrophages that leads to a prothrombotic milieu in the lungs, which can result in thrombosis in situ or pulmonary embolism in susceptible individuals (Figure 1 ).…”
mentioning
confidence: 72%